Latin poetry - Ariosto, Ludovico 1474-1533 (I Tatti Renaissance library, 2018)
Arguably the most important Italian poet of the Renaissance and perhaps the most important European writer before Shakespeare, Ariosto's fame deservedly rests on his narrative poem, Orlando Furioso. In it Charlemagne's war against the Saracens serves as a backdrop to explore typical Renaissance themes such as love, madness, and fidelity, with an elaborate subplot that dramatizes how these themes affect the dynastic fortunes of Ariosto's patrons in the House of Este. The poem was published in over one hundred editions by 1600, so great was its popularity. The additional works that Ariosto composed have inevitably come to be viewed as minor in comparison to the magnitude and renown of his big poem. They include 214 letters, five plays, seven satires in verse, and dozens of lyric poems in Italian and Latin